Influence of Political, Social, Historical, and Natural Resources on Conflicts and Economic Devastations in Mogadishu, Somalia - Ibrahim, Yahya Amir Hagi (2020)
This research investigated the influence of political, social, historical, and natural resources in conflicts and economic devastations in Mogadishu, Somalia. The study employed the Conflict Theory, the Elite Theory of Power and the New War Theory. The conceptualisation focused on politics, social characteristics, natural resources, historical factors variables, and their effect on conflict and economic devastation in the country. The research site was sixteen (16) administrative districts located within Mogadishu, the capital city of Somalia. A sample size of 320 participants was recruited from the selected districts. Probability-sampling techniques were employed to minimise biases. Primary data was collected through structured questionnaires and interviews. The data collected during fieldwork was subjected to both quantitative and qualitative analysis techniques using the Statistical Package for the Social Sciences (SPSS) tool and thematic analysis, respectively. The findings indicate that politics in Somalia have led to civil wars and protracted violent conflicts and that ethnic manipulation, political exclusion, chronic marginalisation and neglect, and manipulation of state resources are risk factors inciting ethnic violence in Somalia. Further, on examining the social characteristics, the findings have shown a correlation value of -0.322, and the significant value was 0.000, which is less than 0.05, translating that any negative change in social characteristics of areas most affected by war would escalate conflicts and economic devastation in Somalia. The study found a relationship between Somalis' natural resources and conflicts and economic devastation in Somalia as shown by a correlation value of -0.212, the significant value was 0.001, which is less than 0.05, and this reveals that any negative change in the role of various natural resources would escalate conflicts and economic devastation in Somalia. On the other hand, a correlation coefficient was recorded on historical factors leading to conflict and economic devastations in Somalia as shown by a correlation value of -0.212, the significant value was 0.001, which is less than 0.05, and this reveals that any negative change in historical factors leading to conflict would escalate conflicts and economic devastation in Somalia. Based on the study findings, the study concludes that Somalia is the epitome of a politically fragile state, which poses a major challenge to the Somali government and the international community. Historical divisions along clan lines and competition for political and clan leadership positions have resulted in violent conflicts among the Somali people. Scarcity and in-abundance of natural resources significantly contribute to violent conflict, based on the political and socio-economic conditions at play, deterioration of social amenities, mainly in areas most affected by war, reduced average economic growth and increased state fragility in Somalia. There is a need to promote political stability in the region in order to ensure economic growth in Somalia; the government of Somalia needs to focus on not only ending violence but also removing the root causes of instability and creating the conditions necessary for peace. Given that historical and cultural sensitivity plays a significant role in ensuring economic growth in Somalia, the Somali government needs to consider the important unifying role of clannism. There is also a need to institute policies that govern the country's exploitation of natural resources and trade.